Gastric cancer-derived exosomal miR-519a-3p promotes liver metastasis by inducing intrahepatic M2-like macrophage-mediated angiogenesis - Shengkui Qiu; Li Xie; Chen Lu; Chao Gu; Yiwen Xia; Jialun Lv; Zhe Xuan; Lang Fang; Jing Yang; Lu Zhang; Zheng Li; Weizhi Wang; et al. (figshare, 2022)
Abstract Background Liver metastasis (LM) is a major obstacle to the prognosis of gastric cancer (GC) patients, but the molecular mechanism underlying gastric cancer liver metastasis (GC-LM) remains unknown. Exosomes have been identified as an important mediator of communication between tumor cells and the microenvironment. Therefore, we sought to investigate the effects of primary GC cells on the liver microenvironment and the role of exosomal microRNAs (exo-miRNA) in GC-LM. Methods Sequential differential centrifugation, transmission electron microscopy and NanoSight analysis were used to extract and characterize exosomes. MicroRNA sequencing in GC-derived exosomes and mRNA sequencing in PMA-treated THP-1 cells were used to identify differentially expressed miRNAs in exosomes and the functional targets of exosomal miR-519a-3p (exo-miR-519a-3p) in macrophages, respectively. Tracing and internalization of exosomes and transfer of exo-miR-519a-3p were observed by immunofluorescence. Tubule formation assays, aortic ring assays, and exosome-educated GC-LM model were used to investigate the roles of GC-derived exosomes and exo-miR-519a-3p in angiogenesis and GC-LM. Luciferase reporter assay, qRT-PCR, Western blot, ELISA, flow cytometry and immunofluorescence were used to investigate the regulatory mechanism of exo-miR-519a-3p at GC-LM. Results The expression level of miR-519a-3p in serum exosomes was significantly higher in GC-LM patients than in patients without LM, and high expression of exo-miR-519a-3p indicates a worse prognosis. GC-derived exosomes are mainly accumulated in the liver and internalized by intrahepatic macrophages. Mechanistically, exo-miR-519a-3p activates the MAPK/ERK pathway by targeting DUSP2, thereby causing M2-like polarization of macrophages. M2-like polarized macrophages accelerate GC-LM by inducing angiogenesis and promoting intrahepatic premetastatic niche formation. Conclusions Our results indicate that exo-miR-519a-3p plays a critical role in mediating crosstalk between primary GC cells and intrahepatic macrophages and is a potential therapeutic target for GC-LM.
Keywords: Biochemistry; Cell Biology; Genetics; Molecular Biology; Physiology; Chemical Sciences not elsewhere classified; Immunology; Biological Sciences not elsewhere classified; Cancer; Infectious Diseases; Virology